2019
DOI: 10.1097/ico.0000000000001961
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of Exposure Keratopathy Across Different Intensive Care Units

Abstract: Purpose: To determine the prevalence and risk factors of exposure keratopathy (EK) across different intensive care units (ICU) at Columbia University Medical Center, including the Pediatric ICU (PICU), Medical ICU (MICU), and Neurologic ICU (NICU). Methods: In this prospective cohort study, 65 patients were examined daily during their admission in the PICU (27 patients), MICU (15 patients), and NICU (23 patients). Data on eyelid position, conjunctival a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 20 publications
1
27
0
1
Order By: Relevance
“…Non-specificity of the ocular manifestations is another concern in the meta-analysis. Due to morbidities such as severe pneumonia and intensive care admission, several patients may develop non-specific conditions such as dry eyes, pain, chemosis and redness [49][50][51]. These features may not be directly related to the underlying disease, and may be observed in severely ill subjects.…”
Section: Plos Onementioning
confidence: 99%
“…Non-specificity of the ocular manifestations is another concern in the meta-analysis. Due to morbidities such as severe pneumonia and intensive care admission, several patients may develop non-specific conditions such as dry eyes, pain, chemosis and redness [49][50][51]. These features may not be directly related to the underlying disease, and may be observed in severely ill subjects.…”
Section: Plos Onementioning
confidence: 99%
“…Hartford et al . [ 1 ] reported EK in 19%, 60%, and 48% of cases in the Pediatric Intensive Care Unit (PICU), Medical Intensive Care Unit (MICU), and Neonatal Intensive Care Unit (NICU), respectively. Another study reported that the prevalence of EK was 27.3%.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure keratopathy (EK) is a common problem among unconscious patients in Intensive Care Units (ICUs). [ 1 ] As a clinical syndrome, EK is characterized by the incomplete closure of the eyelids and defective tear film which lead to corneal injury. [ 2 ] In clinical examination, EK is characterized by irregular tiny abrasions of the inferior half of the cornea.…”
Section: Introductionmentioning
confidence: 99%
“…La lesión corneal observada en el presente estudio fue menor a la reportada por Hartford J y cols que encontraron 19% de lesiones corneales por exposición en un grupo de 27 pacientes en la unidad de cuidados intensivos pediátricos. Esta diferencia puede deberse al azar considerando el escaso (9) número de pacientes pediátricos incluidos . La lesión corneal en las terapias muchas veces no es reconocida por lo que cada centro hospitalario que maneje pacientes críticos debe desarrollar sus protocolos para el cuidado ocular.…”
Section: Discussionunclassified